Environment, development and poverty: a report of the international workshop on India’s forest management and ecological revival - Lele, U.; Mitra, K.; Kaul, O.N. (1995)
India is vast, diverse and complex, in its environments and in environment-society relations. These relationships, and government policies which influence or control them, are the subject of very significant reforms currently occurring in India. At the most fundamental level, this report asks "Who is to protect, manage and regenerate India’s forests, where and for what, and what resources or support does each agent need to fulfil the mandate efficiently and equitably?" The conventional forestry systems have been under scrutiny. "Forestry" no longer means just industrial timber production by the Government, on government-owned lands. Other priority objectives (e.g. ecological and social sustainability) and other participants (farmers, communities, NGOs and industries) have emerged, and new modes of organisation are being explored and tested, such as Joint Forest Management. Is there a contradiction between "new goals and directions, such as JFM", but the old rules, structures and personnel? Is it possible to achieve the opposite goal with virtually the same apparatus as the 1950s? Or has it really beenreformed? What further reforms and support (e.g. education, research, extension and investment funds) are required?